2019
DOI: 10.3389/fpsyg.2019.00710
|View full text |Cite
|
Sign up to set email alerts
|

Red Wood Ants Display Natural Aversive Learning Differently Depending on Their Task Specialization

Abstract: The adaptive benefits of individual specialization and how learning abilities correlate with task performance are still far from being well-understood. Red wood ants are characterized by their huge colonies and deep professional specialization. We hypothesized that red wood ants Formica aquilonia form aversive learning after having negative encounters with hoverfly larvae differently, depending on their task specialization. We tested this hypothesis, first, by examining whether hunters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For example, some species exhibit age-related repertoire expansion, whereas, in others, workers of certain ages have strong tendencies to perform specific tasks (reviews in Hölldobler and Wilson, 2009;Giraldo and Traniello, 2014). In other species, task specialization among workers may be shaped by their size polymorphism, genetic background, experience, and social interactions, which is also partly influenced by age (review in Iakovlev and Reznikova, 2019). The allocation of workers to various tasks may depend on external cues, such as interactions among ants and changes in the environment (Gordon, 2016).…”
Section: Personality At the Colony Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some species exhibit age-related repertoire expansion, whereas, in others, workers of certain ages have strong tendencies to perform specific tasks (reviews in Hölldobler and Wilson, 2009;Giraldo and Traniello, 2014). In other species, task specialization among workers may be shaped by their size polymorphism, genetic background, experience, and social interactions, which is also partly influenced by age (review in Iakovlev and Reznikova, 2019). The allocation of workers to various tasks may depend on external cues, such as interactions among ants and changes in the environment (Gordon, 2016).…”
Section: Personality At the Colony Levelmentioning
confidence: 99%
“…Experiments with other intruders, such as spiders and parasitic rove beetle, revealed a context-dependent specialization in colony defense in F. rufa: small workers were better at preventing brood predation than larger workers, and nurses and workers at nest entrances were more aggressive toward parasitic beetles than foragers (Parmentier et al, 2015). Recently, Iakovlev and Reznikova (2019) showed that in red wood ants F. aquilonia, members of various professional groups form aversive associations with different strengths and speeds. The authors examined whether hunters and aphid milkers learn to avoid the irritating encounters with their enemy (hoverfly larvae) differently.…”
Section: Behavioral and Cognitive Specialization In The "Leader-scouting" Ant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…These individuals should also have more flexible learning abilities and rely more on personal information. Foragers who vary in their foraging strategies as in Ectatomma ruidum (McGlynn et al, 2015) or in their resource specialization as in Formica aquilonia (Iakovlev and Reznikova, 2019) should also vary in their personality traits and cognitive abilities. Since the task repertoire of individual ants changes with age, further studies are also required to understand whether personality traits of individuals remain constant across their lifetimes and how this affects their task choice and task performance at different stages of their life.…”
Section: Future Directionsmentioning
confidence: 99%